Implementasi program Dilan Care sebagai Layanan Peduli Narapidana Disabilitas dan Lanjut Usia di Lembaga Pemasyarakatan Kelas IIA Serang - Siti Dila Riyatul Bahiroh; Yeni Widyastuti; Teguh Aris Munandar (Epistemik Press, 2026)
This study aims to determine the implementation of the Dilan Care program at the Class IIA Serang Penitentiary. Dilan Care is a program specifically designed to meet the basic needs of disabled and elderly inmates at the Class IIA Serang Penitentiary. The program consists of three services: Wisma Dilan, Dilan Clinic, and Dilan Update. The theory used in this study is Merilee S. Grindle's implementation theory, which encompasses nine main components across two dimensions: policy content and implementation context. A qualitative descriptive method was employed through interviews, observations, and documentation at the Class IIA Serang Penitentiary. The results indicate that, in terms of policy content, the interests of key actors, such as inmates and correctional officers, have been addressed, but this has not been optimally achieved due to limited human resources, budget, and infrastructure. The Dilan Care program has provided tangible benefits in the form of more inclusive services, although some services, such as the Dilan Clinic and Dilan Update, have been discontinued. From the context of implementation, strategic decision-making remains centralized within the Directorate General of Corrections, program implementers lack equitable competencies, and internal coordination needs to be strengthened. The bureaucratic organizational structure, family-like work culture, and internal and external oversight all influence implementation effectiveness. Overall, staff compliance and responsiveness to procedures are considered good. Dilan Care has been implemented with high commitment, but requires more adequate policy support and resources for the program's sustainability and optimal performance. Keywords: Dilan Care, Disabilities, Older Adults.